-2(z-11/5)=3z

Simple and best practice solution for -2(z-11/5)=3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(z-11/5)=3z equation:


(5/6)*x-(7/8) = (1/6)*x-(1/4)

(3/2)*x+4*x-3 = 1/3

(x-((1/3)*x))^2 = 0

-5/4 = 10

((3*x)^7)/3

See similar equations:

| 2x^2-6x-9=89 | | 18=-8x+6x | | 7+6x+6x=47 | | 4x^2-16x-33=0 | | 5/6x-7/8=1/6x-1/4 | | 3/2x-(3-4x)=1/3 | | 3(3)+2(5)=60x-500 | | 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 | | (x-1/3x)^2 | | 2x^3+6x^2=1 | | x=2(x+29) | | -54x=10 | | x=2x+58 | | 17x-6=10x-13 | | p=2x+58 | | 48*38= | | x=6+9 | | 7x-2-2x+5=-2x+1+6x | | 1.52=3.16(y-8.62) | | 1.52=(y-8.62) | | ydx=(3x-y^3)dy | | 6n+9=-3n-27 | | y=0.25(x-5)(x-1) | | (x)(x)+3x+2= | | ydx-(3x-y^3)dy=0 | | 2.3x+14= | | n/3=5n-42 | | (p/2)/2 | | 3+3=8x+23 |

Equations solver categories